Study of the solubilisation process of bacterial model membranes induced by DDAO - Želinská K.; Gallová J. (Sciendo, 2021)
Solubilisation of two bacterial model membranes induced by N,N-dimethyl-1-dodecanamine-N-oxide (DDAO) was studied. The first model membrane consisted of a mixture of palmitoyloleoylphosphatidylethanolamine (POPE) and palmitoyloleoylphosphatidylglycerol (POPG) in a molar ratio 0.6:0.4 mol/mol, and a second model membrane was enriched with tetraoleoylcardiolipin (TOCL) with a composition POPE-POPG-TOCL = 0.67:0.23:0.1 mol/mol/mol. Solubilisation of these model membranes was studied by static light scattering (nephelometry). Effective ratio Re (the amount of DDAO integrated into the bilayer to the amount of lipid) at different steps of the solubilisation process was determined. The molar partition coefficient of DDAO was calculated - in case of the POPE-POPG membrane, Kp = 5,300 ± 400, for the POPE-POPG-TOCL membrane, Kp = 6,500 ± 500.